The IL-17A rs2275913 single nucleotide polymorphism is associated with protection to tuberculosis but related to higher disease severity in Argentina - Rolandelli, Agustin (2017)
Mycobacterium tuberculosis (Mtb) causes nearly 10 millions of new tuberculosis disease cases annually. However, most individuals exposed to Mtb do not develop tuberculosis, suggesting the influence of a human genetic component. Here, we investigated the association of the rs2275913 SNP (G → A) from IL-17A and tuberculosis in Argentina by a case-control study. Furthermore, we evaluated in vitro the functional relevance of this SNP during the immune response of the host against Mtb and analyzed its impact on clinical parameters of the disease. We found an association between the AA genotype and tuberculosis resistance. Additionally, within the healthy donors population, AA cells stimulated with a Mtb lysate (Mtb-Ag) produced the highest amounts of IL-17A and IFN-γ, which further support the genetic evidence found. In contrast, within the tuberculosis patients population, AA Mtb-Ag stimulated cells showed the lowest immunological parameters and we evidenced an association between the AA genotype and clinical parameters of disease severity, such as severe radiological lesions and higher bacilli burden in sputum. Overall, our findings demonstrated that the AA genotype from the IL-17A rs2275913 SNP is positively associated with protection to active tuberculosis but related to higher disease severity in the Argentinean population.